Vibhaṅgappakaraṇa : Abhidharmapiṭakayehi deveni granthaya - Sumanasāra, Karahampiṭigoḍa, Sthavira, 1920-; Laṅkānanda, Labugama, 1902-; Laṅkā Bauddha Maṇḍalaya ([Colombo] : Śrī Laṅkā Janarajaya, 1975)
Buddhist canon.
Includes index.
Added t.p. in English.
In Pali (Sinhalese script); parallel translation and prefatory matter in Sinhalese.
Mode of access: Internet.
2
Keywords: Abhidharma